Pemodelan Sistem Data Terdistribusi Untuk Mengintegrasikan Data Akademik Dan Keuangan - Tohir, Arik Sofan (INTENSIF: Jurnal Ilmiah Penelitian dan Penerapan Teknologi Sistem Informasi, 2017)
Data is something that is very important specifically for the needs of a company or organization, which from the data can produce a useful information for the company or organization as a material for development as well as for data analysis as the basis for decision-making. With the development of the world of digital technology is growing nowadays, the data originally stored in paper form can now be stored in digital form by utilizing database engine. If a company or organization already has data scattered in several separate places or developed with several different types of software platforms. Of course, a technique is required to integrate data from several different places and use different types of software platforms. With the existence of this data integration it is possible to combine separate data in multiple places and use several different types of software platforms.